Explanation, prediction, and confirmation - Dieks, Dennis (The philosophy of science in a European perspective, 2011)
Literaturangaben
"Contains selected papers from the workshops organised by the ESF Research Networking Programme PSE (The Philosophy of Science in a European Perspective) in 2009"
Keywords: Konferenzschrift; Wissenschaftstheorie